The Gut Microbiome During Pregnancy. Issue 1 (3rd January 2023) - Jiang, Guoqing; Zhou, Zhiyi; Li, Xiaojuan; Qian, Yuan; Wang, Kunhua
Abstract: Gut microbiota is symbiotic and interdependent with human body. Intestinal probiotics are colonized in the human gastrointestinal tract, which can improve the host intestinal microenvironment and enhance the intestinal function and immune function of the human body. A small number of opportunistic pathogens exist in the intestinal tract. Once the number of pathogens exceeds the threshold of intestinal tolerance, the intestinal micro-ecological balance can be destroyed, and various diseases may thus develop. Pregnancy is a special status with different physiologic changing stages. In the meanwhile, alterations in the gut microbiome populations occur, which can promote the differentiation, development, and maturation of fetal organs by affecting maternal metabolism. Compared with normal pregnant women, great changes in the gastrointestinal function and gut microbiome may take place in pregnant women with pregnancy-related complications, in which these changes include the number, species, and intestinal translocation. The composition of the maternal gut microbiome could contribute to pregnancy and obstetric outcomes, and long-term health of mother and child. The relationships of pregnancy to gut microbiome have attracted an increasing attention in recent years. This article will provide a summary review of the research studies of gut microbiome in normal pregnant women versus abnormal pregnancy women with complications.